Building legitimacy by criticising the pharmaceutical industry: a qualitative study among prescribers and local opinion leaders (Swiss Medical Weekly, 2015)
PRINCIPLES: The literature has described opinion leaders not only as marketing tools of the pharmaceutical industry, but also as educators promoting good clinical practice. This qualitative study addresses the distinction between the opinion-leader-as-marketing-tool and the opinion-leader-as-educator, as it is revealed in the discourses of physicians and experts, focusing on the prescription of antidepressants. We explore the relational dynamic between physicians, opinion leaders and the pharmaceutical industry in an area of French-speaking Switzerland. METHODS: Qualitative content analysis of 24 semistructured interviews with physicians and local experts in psychopharmacology, complemented by direct observation of educational events led by the experts, which were all sponsored by various pharmaceutical companies. RESULTS: Both physicians and experts were critical of the pharmaceutical industry and its use of opinion leaders. Local experts, in contrast, were perceived by the physicians as critical of the industry and, therefore, as a legitimate source of information. Local experts did not consider themselves opinion leaders and argued that they remained intellectually independent from the industry. Field observations confirmed that local experts criticised the industry at continuing medical education events. CONCLUSIONS: Local experts were vocal critics of the industry, which nevertheless sponsor their continuing education. This critical attitude enhanced their credibility in the eyes of the prescribing physicians. We discuss how the experts, despite their critical attitude, might still be beneficial to the industry’s interests.